Educational Transformation: Implementation of Technology-Based Learning Models in Improving Critical Thinking Skills in Boarding School Environments - Nadira Putri Valencia; Sadam Fajar Shodiq (Yayasan Keluarga Guru Mandiri, 2024)
Implementing technology-based learning models is crucial for fostering students' critical thinking skills inside a school dormitory setting. This research aims to assess the impact of technology-based learning models on the development of students' critical thinking skills at boarding schools located in Yogyakarta. This research included a sample of 298 students from boarding schools in Yogyakarta. This research employed quantitative methodologies, namely utilizing a Likert scale survey. Four boarding schools were included in this research. Researchers used the SmartPLS version 4 technology to conduct experiments and validate this notion. The research results demonstrate that the utilization of technology in learning has a beneficial impact on students' aptitude for critical thinking. Implementing technology-based learning methods in boarding schools is essential to maintain a harmonious integration of technological advancements. However, it is sufficient for students to enhance their critical thinking skills.